Evidence to practice – lessons learnt in developing an implementation strategy for an online digital health intervention (Eczema Care Online) - Laura Howells; Kim S. Thomas; Miriam Santer; Ingrid Muller; Kate Greenwell; Amanda Roberts; Hywel C. Williams; Jane Harvey; Stephanie J. Lax; Natasha K. Rogers; Tracey H. Sach; Sandra Lawton; et al. (BMC Health Services Research)
Abstract Background Eczema Care Online ( www.EczemaCareOnline.org.uk/ ) is an online self-management toolkit which includes tailored content for young people (13–25 years) and for parents of children that have eczema (0–12 years). Testing in two randomised controlled trials has shown that it is easy to use, cost effective and offers a sustained improvement in eczema symptoms. Implementing Eczema Care Online outside of a funded research study and ensuring that it reaches those that will most benefit from is now a key challenge. This paper describes the lessons learnt from developing and delivering an implementation strategy. Methods Data from systematic reviews, stakeholder consultation meetings, interviews with trial participants, intervention usage data during the trial, and existing eczema information websites informed our implementation plan. Using Normalisation Process Theory, an implementation plan combined these findings with practical, context-specific actions to encourage wider adoption of the intervention. Results Data was successfully mapped to the four constructs of Normalisation Process Theory, and factors and processes that encourage implementation identified. These include: promoting how Eczema Care Online is different to other sources of information; aligning to and embedding in existing eczema resources (from charities and healthcare providers); simplifying aspects to aid ease of use; and, highlighting evidence that shows that Eczema Care Online works. Key lessons in developing an implementation strategy include 1) start implementation work early 2) maintain flexibility to explore multiple routes to implementation 3) use secondary data sources 4) balance theory with practicalities 5) consider longer-term maintenance beyond the life of the research project. Conclusion Implementation planning is a key stage of the research process that is often not adequately resourced. Implementation planning ensures effective interventions developed and evaluated in research studies are utilised in everyday practice.